Answer:
For k = 6 or k = -6, the equation will have exactly one solution.
Step-by-step explanation:
Given a second order polynomial expressed by the following equation:
[tex]ax^{2} + bx + c, a\neq0[/tex].
This polynomial has roots [tex]x_{1}, x_{2}[/tex] such that [tex]ax^{2} + bx + c = (x - x_{1})*(x - x_{2})[/tex], given by the following formulas:
[tex]x_{1} = \frac{-b + \sqrt{\bigtriangleup}}{2*a}[/tex]
[tex]x_{2} = \frac{-b - \sqrt{\bigtriangleup}}{2*a}[/tex]
[tex]\bigtriangleup = b^{2} - 4ac[/tex]
If [tex]\bigtriangleup = 0[/tex], the equation has only one solution.
In this problem, we have that:
[tex]3x^{2} + kx + 3 = 0[/tex]
So
[tex]a = 3, b = k, c = 3[/tex]
[tex]\bigtriangleup = b^{2} - 4ac[/tex]
[tex]\bigtriangleup = k^{2} - 4*3*3[/tex]
[tex]\bigtriangleup = k^{2} - 36[/tex]
We will only have one solution if [tex]\bigtriangleup = 0[/tex]. So
[tex]\bigtriangleup = 0[/tex]
[tex]k^{2} - 36 = 0[/tex]
[tex]k^{2} = 36[/tex]
[tex]k = \pm \sqrt{36}[/tex]
[tex]k = \pm 6[/tex]
For k = 6 or k = -6, the equation will have exactly one solution.